Mount Sacred A Brief Global History of Holy Mountains Since 1500 - Mathieu, Jon (The White Horse Press, 2023)
Mount Kailash in Asia, the Black Hills in North America, Uluru in Australia: around the globe there are numerous mountains that have been and continue to be attributed sacredness. Worship of these mountains involves prayer, meditation and pilgrimage. Christianity, which for a long time showed little interest in nature, provides a foil to these practices and was one factor in the tensions that arose in the age of colonialism. Decolonisation and the 'ecological turn' changed the religious power of interpretation and gave discourses about sacred mountains new meaning. Globally, however, they remain an outstanding example of cultural diversity, also touching on issues of gender justice and environmental protection. A translation from the original German.